2011
DOI: 10.1155/2011/179674
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapies for Obesity: Past, Current, and Future Therapies

Abstract: Past therapies for the treatment of obesity have typically involved pharmacological agents usually in combination with a calorie-controlled diet. This paper reviews the efficacy and safety of pharmacotherapies for obesity focusing on drugs approved for long-term therapy (orlistat), drugs approved for short-term use (amfepramone [diethylpropion], phentermine), recently withdrawn therapies (rimonabant, sibutamine) and drugs evaluated in Phase III studies (taranabant, pramlintide, lorcaserin and tesofensine and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
137
0
9

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(146 citation statements)
references
References 128 publications
0
137
0
9
Order By: Relevance
“…18 Two anti-obesity drugs have been approved by NICE but subsequently withdrawn: Rimonabant in 2009 4 and Sibutramine in 2010. 13 …”
Section: Withdrawn Pharmacotherapymentioning
confidence: 99%
“…18 Two anti-obesity drugs have been approved by NICE but subsequently withdrawn: Rimonabant in 2009 4 and Sibutramine in 2010. 13 …”
Section: Withdrawn Pharmacotherapymentioning
confidence: 99%
“…Lorcaserin, taranabant, topiramate and bupropion with naltrexone are currently on phase III trials with demonstrated significant weight loss compared to placebo at more than 12 months. Some pharmacotherapies have also demonstrated clinical benefits without any side effects, however, further studies are required for a long-term safety [86]. Recently, contrave, a combination of two approved drugs of bupropio and naltrexone, completed Phase III trials with significant weight loss and was approved by FDA in 2010, but FDA declined to approve contrive due to serious cardiovascular adverse events in 2011 [86].…”
Section: Pharmacological Treatments For Obesity (Orlistat Sibtraminementioning
confidence: 99%
“…Some pharmacotherapies have also demonstrated clinical benefits without any side effects, however, further studies are required for a long-term safety [86]. Recently, contrave, a combination of two approved drugs of bupropio and naltrexone, completed Phase III trials with significant weight loss and was approved by FDA in 2010, but FDA declined to approve contrive due to serious cardiovascular adverse events in 2011 [86]. Importantly, obesity is, at least, in part, determined by genetic backgrounds [87], suggesting that a genetic approach to limiting obesity may find a place in the future.…”
Section: Pharmacological Treatments For Obesity (Orlistat Sibtraminementioning
confidence: 99%
“…Currently licensed drugs, generally aimed at either reducing intestinal fat absorption (such as intestinal lipase inhibitors) or inhibiting appetite (such as phentermine), have limited weight loss efficacy on their own. Anti-obesity agents which elevate EE by stimulating the sympathetic nervous system have produced dangerous side effects, particularly cardiovascular morbidity [2][3][4]. There is a great unmet need for drugs that can safely inhibit appetite and increase EE.…”
Section: Introductionmentioning
confidence: 99%